1981
DOI: 10.1103/physrevlett.47.75
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Decreased Pairing Energies in Odd-NNuclei from Band-Crossing Frequencies

Abstract: An odd-even neutron-number dependence of the alignment frequency of the first pair of t 13 / 2 quasineutrons in rare-earth nuclei is established. This effect is explained by a reduction of the neutron pairing-correlation parameter A" for odd-Af systems as compared to seniority-zero configurations in even-iV nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(9 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…The band crossing frequency is about 40 keV lower than that of the yrast band in the neighboring even-even nucleus 162 Er [37]. This phenomenon was observed in a number of odd-A nuclei in the rare-earth region, and it could be explained by a reduction of neutron pairing correlation [38]. One interesting feature here is that the alignment curves for the two signature branches cross at ω ≈ 0.24 MeV as shown in Fig.…”
Section: A Alignment Propertiesmentioning
confidence: 88%
“…The band crossing frequency is about 40 keV lower than that of the yrast band in the neighboring even-even nucleus 162 Er [37]. This phenomenon was observed in a number of odd-A nuclei in the rare-earth region, and it could be explained by a reduction of neutron pairing correlation [38]. One interesting feature here is that the alignment curves for the two signature branches cross at ω ≈ 0.24 MeV as shown in Fig.…”
Section: A Alignment Propertiesmentioning
confidence: 88%
“…Configuration dependent pairing [18] and interactions between quasiparticles [19] not included in the simple version of the cranked shell model were found in Er, Yb, Hf, and W isotopes. Recently Herskind [20] outlined a new way to estimate these effects from crossing frequencies.…”
Section: Residual Interactionsmentioning
confidence: 97%
“…This article builds upon the classic work of Garrett et al [22] who systematically investigated band-crossing frequencieshω c , associated with the alignment of the first pair of i 13/2 neutrons; (AB) in the nomenclature of Riedinger et al [23]. The band-crossing frequencyhω c corresponds to the point where the Routhians (energy in the rotating frame) of two different quasiparticle configurations cross one another, changing the energetically preferred configuration [18].…”
Section: Data Analysis and Resultsmentioning
confidence: 94%
“…[23], a listing of the quasiparticle assignments to specific neutron orbitals close to the Fermi surface for rare-earth nuclei is given. Garrett et al [22] found evidence was for an odd-even neutron-number dependence,hω c (odd N) <hω c (even N), which was attributed to changes in the strength of neutron pairing correlations. The present paper carries out a similar comprehensive investigation for the second pair of aligning i 13/2 neutrons (BC) occurring at higher rotational frequencies.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%